Memory and utopian agency in utopian/dystopian literature memory of the future - Hanson, Carter F. (Routledge, Taylor & Francis Group, 2020)
Introduction: Memory, Utopian Theory, Counter-Discourse -- A Brief History of Memory's Emergence in Utopian Narratives -- The Critical Utopia and Collective Memory -- Children's/Young Adult Dystopian Fiction and Cultural Amnesia -- Margaret Atwood's MaddAddam Trilogy and the Dialectic of Trauma